Chronostratigraphy of the Aburrá Valley, in Colombia: A review - Noriega-Londoño, Santiago; Arboleda-Giraldo, Mateo; Restrepo-Moreno, Sergio A.; Marín-Cerón, María Isabel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The Aburrá Valley (VA), located in the Central Cordillera of Colombia, is covered by extensive surface formations of various types. These deposits record the morphodynamic response of different tectonic and erosive processes, controlled by humid tropical climatic conditions and recent geodynamic activity of the Northern Andes. This contribution presents a review of the state of the art of the chronostratigraphy of the surface formations of the VA, as a tool to quantify the geomorphological processes responsible for the conformation and evolution of the VA. The compiled data cover an intervalfrom the late Pliocene to the late Holocene, recording the response of the landscape to the last phase of the Andean Orogeny. This review highlights the need to produce new chronological and stratigraphic data in the Quaternary, as a basis for understanding landscape evolution models, and hence procure a coherent approach to hazard assessment studies, risk management strategies and land use planning, particularly in the context of large urban centers of the Andean region.